Innovations in targeting RNA by fragment-based ligand discovery. (April 2023) - Koehn, Jordan T.; Felder, Simon; Weeks, Kevin M.
Abstract: A subset of functional regions within large RNAs fold into complex structures able to bind small-molecule ligands with high affinity and specificity. Fragment-based ligand discovery (FBLD) offers notable opportunities for discovery and design of potent small molecules that bind pockets in RNA. Here we share an integrated analysis of recent innovations in FBLD, emphasizing opportunities resulting from fragment elaboration via both linking and growing. Analysis of elaborated fragments emphasizes that high–quality interactions form with complex tertiary structures in RNA. FBLD-inspired small molecules have been shown to modulate RNA functions by competitively inhibiting protein binding and by selectively stabilizing dynamic RNA states. FBLD is creating a foundation to interrogate the relatively unknown structural space for RNA ligands and for discovery of RNA-targeted therapeutics. Graphical abstract: Image 1 Highlights: Fragment-based ligand discovery holds substantial promise for RNA-targeted therapeutics. Fragment elaboration, either by linking or growing, is essential. Elaboration can be successful without initial high-resolution RNA structural information. Complex RNA motifs form more and higher-quality interactions with small-molecule ligands. Modestly elaborated ligands engage RNA with sub-micromolar affinity and good specificity.